Hubungan Pemakaian Gadget Terhadap Indeks Massa Tubuh (IMT) Siswa SD Maranatha 01 Kota Semarang - Christina Ary Yuniarti; Imam Tri Harsoyo (Indonesian Journal of Health Community, 2025)
The rapid development of information technology, especially in gadgets, has changed people's lifestyles. This study aims to determine the relationship between the duration of gadget use and Body Mass Index (BMI) in students at Maranatha 01 Elementary School, Semarang City. This study used a quantitative, objective approach with a sample of 42 respondents. Parameters measured included height and body mass using an automatic BMI tool. Next, questionnaires were collected, and data were analyzed using the chi-square test and linear regression. The results showed that the majority of students used gadgets for less than two hours per day and began using gadgets after the age of five. According to the analysis, there was no significant relationship between the duration of device use and students' BMI status (p=0.721), and the effect was very weak in the regression analysis (p=0.729). This suggests that time spent using devices is not the primary factor influencing children's BMI. Other factors such as diet, physical activity levels, and genetic predisposition play a greater role in determining children's nutritional status. It is hoped that this research will serve as a basis for developing more comprehensive child health policies and programs in the modern era.